EIT-based giant self-kerr-nonlinear behavior of multilevel X-scheme. (2020) - Kaur, Amanjot; Dar, Zubair Iqbal; Kaur, Sukhdeep; Kaur, Paramjit
Abstract: This paper aims at theoretical evaluation of enhanced self-Kerr nonlinear coefficient in multilevel X-conformation of 87 Rb atom. The coupled density matrix equations are numerically solved by iterative perturbation method to obtain first- and third-order probe response spectra. It is found that large self Kerr nonlinearity with reduced absorption is obtained at the positions of Electromagnetically induced transparency regions. The maximum value, sign as well as slope of self-Kerr nonlinearity can be manipulated via adjusting detuning parameter corresponding to the strong electromagnetic (e.m.) fields. The controllability of Kerr nonlinear index finds usage in numerous applications like optoelectronic devices, quantum computing and so on. It is also elucidated that Kerr nonlinearity can be escalated by inculcation of Doppler effect.